Effects of Corrosion on Heat Transfer Characteristics of Double-Tube Heat Exchangers - Kwon, Hyun-Min; Choi, Yong-Ki; Kwon, Jeong-Tae; Chul Kwon, Young; Huh, Cheol (Asian Journal of Chemistry, 2015)
This paper presents the effects of corrosion on the performance of double-tube heat exchangers using deep ocean water. Aluminum with/without coatings were possible alternative material tubes for replacing the high-price titanium tubes from the previous reported experiments. In this study, the titanium, aluminum, aluminum with electro-deposition coatings (10, 15, 20 μm) were tested under the condition of pure and corroded tubes. The temperature of sea water 70 °C and the concentration of salt 3.5 % were manufactured by corrosion manufacturing unit. The corrosion periods were 6, 12 and18 weeks, respectively. The comparison of the experimental and analytical results were performed. From these analysis, we could confirm the possibility of aluminum with electro-deposition coating 15 μm when the tubes were corroded for 6 and 12 weeks. But, when the corrosion was conducted for 18 weeks, aluminum with 20 μm coating could be considered as alternative for the replacement of titanium.